Soft tissue facial profile in Himachal population: A photogrammetric analysis - Vikrant Bhandari; Anil Singla; Vivek Mahajan; Harupinder Singh Jaj; Sukhraj Singh Saini (Wolters Kluwer Medknow Publications, 2015)
Introduction: Craniofacial growth of the skeleton and soft tissue influences the final configuration of occlusion and overall facial esthetics. Materials and Methods: Two hundred samples were taken from Himachali ethnic population with age ranging from 18 to 28 years. The records will then be scaled to life size and landmarks will be located on the digitized image to obtain all linear and angular measurements. Results: The parameters were analyzed using SPSS Statistics Software version 11.5. Student's t-test was conducted for comparison between male and female subjects. The reproducibility of the measurements was analyzed using Dahlberg's (1940) formula. To determine the difference between two measurements, made at least 2 months apart, 25 randomly selected records were redigitized. Conclusion: Himachali males and females show considerable sexual dimorphism with less prominent nose, less protrusive lower lip, and more chin height in males whereas females had more convex profile, less protrusive upper lip, and more tipped nose.